DIETITIANS IN RURAL, ACUTE CARE SETTINGS REPORT GREATER LIKELIHOOD OF RECOMMENDING FEEDING TUBES IN DEMENTIA. (11th November 2018) - Douglas, J; Lawrence, J; Turner, L; Knol, L; Ellis, A
Abstract: While current guidelines advise against feeding tubes (FT) for individuals with advanced dementia (AD), FT use is common in this population. This study sought to determine whether the geographic region and rural/urban healthcare setting were associated with Registered Dietitians (RDs) recommending a FT for a patient with AD. Researchers surveyed a random sample of 4, 936 clinical RDs in the United States. Participants indicated their work setting, their likelihood of recommending a FT in AD, their facility's geographic region, and whether their facility is rural, urban, or suburban. Chi-square tests determined whether RD recommendations varied by geographical characteristics. Of 580 RDs who stated they were either likely or unlikely to recommend a FT in AD, fewer RDs in long-term care settings recommended a FT compared to those in acute care settings and other settings (7.8%, 21.1%, and 28.6%, respectively, p < .001), but no differences were seen by region or rural/urban location. Considering only long-term care RDs, there were no differences by region or rural/urban location. Acute care RDs did not differ by region, but more acute care RDs in rural settings recommended a FT than those in suburban or urban settings (29.8%, 24.1%, and 13.1%, respectively, p = .033). Compared to those in other settings, more RDs in rural, acute care settings recommended FTs for a patient with AD. While more research is needed to fully understand these findings, these results provide direction for educational interventions to reduce FT use in patients with AD.